Non-linear Analysis and Shear Effect in Cable-Stayed Bridges - Singh P.K.; Upadhaya C.B.; Agrawal T.P. (My University, 2025)
Cable-stayed bridges are gaining quick popularity and are now generally believed to be better than suspension bridges in the span range of 100 m to 1000 m. Even if, materials in a cable-stayed bridge behave as linearly elastic, the bride exhibits nonlinear behavior due to its inherent flexibility. This nonlinear behavior of cable-stayed bridges is due to cable sag, beam-column interaction and change of geometry. These nonlinearities and effect of shear deformation in cable-stayed bridge analysis are investigated treating the bridge as 2-dimensional and using basically stiffness matrix method. It is found that nonlinearity is highly dependent on cable stress level. However, with adequate cable stress individual maximum nonlinearities due to cable slag, beam-column interaction and change of geometry for the analyzed steel bridge cases are of the order of 2.2%, 1.2% and 1.5%, respectively, and the maximum effect of shear deformation is also of the other of 2.0%. Thus, it is inferred that along with the nonlinear analysis, the effect of shear deformation must also be considered. Maximum combined nonlinearity due to all the three sources and the shear effect, for live load being applied on the pre-tensioned bridge, is found to be of the order of 2.5% provided the cables are reasonably well stressed.